2018
DOI: 10.1016/j.ejvs.2018.03.016
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Laser in situ Fenestration of Current Aortic Endografts

Abstract: This study demonstrates that both LISF and MISF create substantial damage to all available endograft fabrics. Until comparisons with reinforced fenestrations are performed, LISF and MISF should not be used outside investigational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Recent work demonstrates that both laser and mechanical in situ fenestrations cause substantial damage to all available stent-graft fabrics. 219 The multilayer (or flow modulator) technique has recently been advocated for the treatment of various thoracic and abdominal aortic pathology including the aortic arch. The principle of the technique is formed by a self-expanding multilayered stent constructed of cobalt alloy wires interconnected in 5 layers.…”
Section: Classmentioning
confidence: 99%
“…Recent work demonstrates that both laser and mechanical in situ fenestrations cause substantial damage to all available stent-graft fabrics. 219 The multilayer (or flow modulator) technique has recently been advocated for the treatment of various thoracic and abdominal aortic pathology including the aortic arch. The principle of the technique is formed by a self-expanding multilayered stent constructed of cobalt alloy wires interconnected in 5 layers.…”
Section: Classmentioning
confidence: 99%
“…Third, a 5 × 5 mm prefenestration on Valiant Stent Grafts then engaged with stent grafts was confirmed safety and integrity in a 5-year stimulated fatigue test and a median 38.9-month clinical follow-up. Although in-vitro experiment showed that a laser or needle effectively generated a hole in the membrane, the controllability was severely affected by the aortic pulsation in vivo ( 24 , 27 ). The laser may cause serious damage to the membrane, which resulted in junction weakness and gutter leakage ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although in-vitro experiment showed that a laser or needle effectively generated a hole in the membrane, the controllability was severely affected by the aortic pulsation in vivo ( 24 , 27 ). The laser may cause serious damage to the membrane, which resulted in junction weakness and gutter leakage ( 27 ). In the fatigue test of this study, no obvious damage was found beyond the fenestration at 262,800,000 cardiac cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Fenestration using laser energy is favorable for the following reasons: (1) perforation is reproducible and efficient, (2) the need for cutting balloon (and associated destruction) is obviated, and (3) laser fenestration can reliably perforate most graft material (ie, PET, PTFE, and expanded PTFE [ePTFE]). 2427 The issue of laser fenestration of ePTFE devices demands more in-depth investigation because the literature has focused on plain PTFE only, 17 whereas surface modifications of PET after fenestration are inadequately documented. 28 Regardless, each technique (ie, laser, radiofrequency, or needle) has its strengths and weaknesses, and further head-to-head studies are needed to determine superiority.…”
Section: Discussionmentioning
confidence: 99%